Gastronomic Tourism as an Innovative Strategy to Increase the Attractiveness of Tourist Destinations - Juniarta, Pande Putu; Suta, Putu Wira Parama (Jurnal Informatika Ekonomi Bisnis, 2025)
This study explores gastronomic tourism as an innovative strategy to enhance the attractiveness of tourist destinations. As experiential tourism gains prominence, local culinary experiences have emerged as powerful tools for cultural engagement and destination differentiation. The objective of this research is to examine how gastronomic elements such as traditional dishes, culinary storytelling, and participatory food activities influence tourists’ perceptions, emotional connections, and behavioral intentions. A qualitative method using a systematic literature review was employed, drawing on peer reviewed sources from 2020 to 2024 across disciplines including tourism, marketing, and cultural studies. The analysis identifies four key dimensions destination image, emotional engagement, policy integration, and development challenges as critical to the success of culinary tourism strategies. The findings show that gastronomy contributes not only to sensory satisfaction but also to cultural identity formation and emotional bonding, particularly when integrated with tourism policy frameworks. However, challenges such as limited local capacity and policy fragmentation persist in emerging destinations. The study concludes that strategic incorporation of gastronomy into tourism development can drive sustainability, competitiveness, and cultural preservation. Recommendations for future research include empirical validation and inclusive policy design to empower local communities through food based tourism.